SELECTED ASPECTS OF EDITING POST-WAR AND CONTEMPORARY DRAMAS IN PRINT AND DIGITAL FORMATS - Kramkowska-Dąbrowska, Agnieszka (Prace Polonistyczne, 2025)
What may serve as a starting point for discussing various aspects of editing post-war and contemporary dramatic works are unique features of drama as a literary text – one that presents the author’s vision of its stage performance. The first part of the article focuses on the works of writers, such as Janusz Krasiński, Władysław Terlecki, Henryk Bardijewski, and Roman Brandstaetter, whose dramas were published in the series titled “Dramat Polski. Reaktywacja” (“Polish Drama. Reactivation”). The examples that are examined show a tendency of dramatic works to change and evolve, which is related to their adaptation to various media: theatre, radio, and television. The article also examines the consequences that this poses for editors, including a necessity for extensive archival research, the unclear status of the theatrical copy, and the difficulties in cataloguing the diverse versions of the text. Kramkowska-Dąbrowska also discusses another important aspect of the editor’s work on dramas: the preparation of stage directions for publication. The second part of the article describes the concept and objectives of the Cyfrowa edycja polskiego dramatu powojennego i współczesnego (Digital Edition of Polish Post-War and Contemporary Drama), developed alongside the print series as part of the same project. Then, the methods used in creating the digital edition are compared to traditional editing. In both cases the process starts with the analysis of the text and its sources. Kramkowska-Dąbrowska emphasizes the role of textual research and editorial accuracy in preparing digital editions and explains how textual research may shape the process of creating digital editions.